SALES PREDICTION OF ANUGERAH JAYA PANCING 99 SHOP WITH BACKPROPAGATION NEURAL NETWORKS - Binurilfatikhah, Barikna; Hastono, Tri; Sulistyawati, Tyas (JTH: Journal of Technology and Health, 2023)
Artificial Neural Network (Artificial Neural Network) is an information processing paradigm inspired by the workings of biological nervous systems, such as the performance of the brain, which processes information. Toko Anugerah Jaya Pancing 99 faces challenges in predicting product sales that fluctuate according to customer demand, and external factors can also affect sales of their products. To determine store sales predictions using the backpropagation method. From the research results with data training experiments it was found that the iterations process stopped when the epoch reached 6, time 0.00.01, performance 0.317, Gradient 0.359, and Validation Checks 6. Keywords: Prediction, Backpropagation, Neural Networks, Sales